The Slovak Health Insurance System and The Potential Role for Private Health Insurance Policy Challenges - Colombo, Francesca (OECD Health Working Papers, 2004)
This paper analyses the Slovak health insurance system and the policy challenges it faces. It describes the structure of health coverage and health sector reforms being implemented by the Slovak government. It provides a preliminary assessment of the possible impact of such reforms, with a focus on the health insurance system and the possible introduction of private health insurance (PHI). It assesses how private health insurance would impact upon the health system, particularly equity, efficiency incentives facing providers and insurers, and responsiveness. The Slovak health system is based upon a mandatory Bismarck-style social health insurance system. Contributions are shared between employers and employees and the state contributes for the inactive population. Five non-profit and non-competing insurers operate nationwide, one of which covers two-thirds of the population. Individuals can freely enrol with any of the insurance companies and a risk equalisation system ...